THE RELATIONSHIP OF DEMOGRAPHIC AND ADMISSION EXAM SCORES WITH FIRST SEMESTER GRADE POINT AVERAGE IN TWO COHORTS OF FIRST YEAR NURSING STUDENTS - Christine Louise Sommers; Grace Wirawan (Belitung Nursing Journal, 2019)
Background: As nursing programs in Indonesia admit students, it is important that student factors are identified that provide information about necessary resources that are needed to support the student, both academically and psychosocially, to succeed in the nursing program.  Obejctive: The purpose of this study was to use regression analysis to analyze admission and academic data of two cohorts of nursing students to know what relationship that information has with first semester grade point average (GPA). Methods: A descriptive correlation design was used. In a previous study with one cohort of nursing students, the researcher found that the variables accounted for only 28% of the variance. This research added the variable of age, increased the categories for region of origin from five to seven, increased the categories for type of high school from three to four, and analyzed the data from two cohorts. Data from 947 students were included for analysis.  Mulivariate linear regression was used to analyze the variables of city of origin, attendance at pre-nursing course, gender, age, type of high school, and admission exam scores to determine the relationship, if any, between the first semester GPA of nursing students in a large university in an urban area of Indonesia.  Results: A significant relationship (p<.05) was found between experience factors, attribute factors, and academic metric factors and first semester GPA. For students admitted in 2016, the study variables accounted for 30% of the variance in GPA; for students admitted in 2017, the study variables accounted for 37% of the variance in GPA. Conclusion: It is important that student factors are identified that provide information about succeeding in the nursing program, both academically and psychosocially.  Additional research is needed to identify other admission factors and any factors in the first semester that may also have a relationship with GPA.